Replacement of Saturated Animal Fats in Meat Products: A Review - Halwai, Anup (Journal of Food Science and Technology Nepal, 2014)
Meat is still the most valuable food in the world. The quality aspect of meat is decided by the nutritional and sensory values. Consumers. awareness on diet and health increased the demand for healthy food, specially, meat. Meat is high in saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA). SFA are found to elevate cholesterol which is associated with cardiovascular diseases and other chronic diseases. Replacing or reducing animal fat in meat products could create a better image for the industry, but, sensory quality as well as product stability could be affected. Animal fat can be replaced or reduced by adding more water in the product or by substituting with vegetable fats and/or oils, or by adding hydrocolloids like dextrins, starches, fibers, gums in the product. Marine oils and vegetable oils are used to replace animal fat in meat product but the technological procedures have to be adjusted to produce the similar product due to their different chemical characteristics from animal fats. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10561 J. Food Sci. Technol. Nepal, Vol. 7 (9-13), 2012